Impact of darolutamide on local symptoms: pre‐planned and post hoc analyses of the ARAMIS trial. (29th September 2022) - Shore, Neal D.; Stenzl, Arnulf; Pieczonka, Christopher; Klaassen, Zachary; Aronson, William J.; Karsh, Lawrence; Ryan, Charles J.; Ortiz, Jorge; Srinivasan, Shankar; Mohamed, Ateesha F.; Verholen, Frank
Abstract : Objective: To assess, the effect of darolutamide (a structurally distinct androgen receptor inhibitor) on urinary and bowel symptoms, using data from the phase III ARAMIS trial (NCT02200614) that showed darolutamide significantly reduced the risk of metastasis and death versus placebo. Patients and Methods: Patients with non‐metastatic castration‐resistant prostate cancer (nmCRPC) were randomised 2:1 to darolutamide ( n = 955) or placebo ( n = 554). Local symptom control was assessed by first prostate cancer‐related invasive procedures and post hoc analyses of time to deterioration in quality of life (QoL) using total urinary and bowel symptoms, and individual questions for these symptoms from the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Prostate Cancer Module subscales and Functional Assessment of Cancer Therapy‐Prostate prostate cancer subscale. Prostate‐specific antigen (PSA) responses were correlated with urinary and bowel adverse events (AEs). Results: Fewer patients receiving darolutamide (4.7%) versus placebo (9.6%) underwent invasive procedures, and time to first procedure was prolonged with darolutamide (hazard ratio 0.42, 95% confidence interval 0.28–0.62). Darolutamide significantly ( P < 0.01) delayed worsening of QoL for total urinary and bowel symptoms versus placebo, mostly attributed by individual symptoms of urinary frequency, associated pain, and interference with daily activities. AEs of urinary retention and dysuria were less frequent with darolutamide, and greater PSA response (≥90%, ≥50% and <90%, <50%) among darolutamide‐treated patients was associated with lower incidences of urinary retention (2.2%, 4.2%, 5.1%) and dysuria (0.5%, 3.2%, 5.1%), respectively. Conclusions: Darolutamide demonstrated a positive impact on local disease recurrence and symptom control in patients with nmCRPC, delayed time to deterioration in QoL related to urinary and bowel symptoms, and a favourable safety profile showing similar incidence of urinary‐ and bowel‐related AEs compared with placebo.